THE INFLUENCE OF E-WALLET FOR PAYMENT TRANSACTION ON IMPULSIVE BUYING BEHAVIOR IN MANADO - Inri Tyvanny Tewu; Joyce Lapian; Maria Tielung (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
Manado, as the one of city with rapid economic growth in Indonesia, not least got the impact of the trend in the use of E-wallet as a payment method. The amount of public interest in the use of E-Wallet as a payment instrument can be seen from the number of E-Wallet circulating and the number of promotions by E-Wallet providers. E-wallet users are given benefits such as vouchers, rebates/discounts, bonuses, merchandise and many more. In partial test, the purpose of this study is to find out the result of how E-wallet as the payment tools affect consumer impulsive buying behavior in Manado. This research type is qualitative analysis method using purposive sampling as the sampling technique, The sample size of this research is the ten customer that using E-wallet as their payment transaction as the informants. Purposive sampling was used to collecting data through the in depth interview by list of questions. The result shows that all of them choosing e-wallet as a payment method. That most informants almost have the same answers about the advantages to use e-wallet because e-wallet is seen as a convenient and relatively easier way for transaction process, moreover the use of e-wallet lowers the perceived cost with bigger future use. It is also discovered that each person of the customer of the ten informants have their own different experiences and opinions for the advantages and disadvantages of using e-wallet that affects impulsive buying behavior. The advantages of e-wallet possession such as promos and discount attract people attention towards the things that they donâ€™t need. From there it can see how much the possession of e-wallet affects their decision-making process to make such an impulsive decision.Â Keywords: E-wallet, Impulsive Buying Behavior